Potential Brain Age Reversal after Pregnancy: Younger Brains at 4–6 Weeks Postpartum. (21st August 2018) - Luders, Eileen; Gingnell, Malin; Poromaa, Inger Sundström; Engman, Jonas; Kurth, Florian; Gaser, Christian
Highlights: Brains at late postpartum were estimated to be younger than at early postpartum. On average, that difference was about five years. These findings suggest a substantial restoration/rejuvenation effect after giving birth. The effect seems to be already evident within 4–6 weeks postpartum. Abstract: Pregnancy is accompanied by complex biological adaptations, including extreme hormonal fluctuations. Moreover, changes on the endocrine level are accompanied by changes in cerebral anatomy, such as reductions in brain or gray matter volume. Since declining brain and tissue volumes are characteristic for normal aging, the question arises of whether such pregnancy-induced anatomical effects are permanent or transient. To answer this question, we acquired high-resolution brain image data of 14 healthy women in their mid-twenties to late thirties at two time points: within 1–2 days of childbirth (early postpartum) and at 4–6 weeks after childbirth (late postpartum). At both time points, we estimated the brain ages for each woman using a well-validated machine learning approach based on pattern recognition. Ultimately, this algorithm – designed to identify anatomical correlates of age across the entire brain – reveals a single score for each individual: the BrainAGE index. Comparing the BrainAGE indices between both time points, female brains at late postpartum were estimated to be considerably younger than at early postpartum. On average, that difference was about five years (mean ± SD: 5.4 ± 2.4 years). These findings suggest a substantial restoration/rejuvenation effect after giving birth, which is evident already within the first couple of months.